Kewenangan Pemerintah Kabupaten/Kota dalam Pengelolaan Sumber Daya Alam di Wilayah Laut Perbatasan Negara - Lumintang, Junior Alvaro Nazario; Pietersz, Jemmy Jefry; Nendissa, Renny Heronia (TATOHI: Jurnal Ilmu Hukum, 2024)
Introduction: Indonesia is one of the largest archipelagic countries in the world with a total of 17,508 islands and borders with other countries. As a country with a number of boundaries with other countries, Indonesia must strategically plan its borders to protect the sovereignty of its own country.Purposes of the Research: This writing aims to re-position the regional government's authority in managing marine natural resources, especially those in border areas.Methods of the Research: The research method used in this study is normative legal research or another name, namely doctrinal law research which uses statutory regulations as the basis for this research. The analysis uses the statutory approach (statute approach), and the conceptual approach (conceptual approach).Result of the Research: The results of this study indicate that in the Indonesian constitution, there is the authority given to Regency/City Governments to manage border areas for the welfare of the surrounding community and Indonesia as a whole. Thus this thesis was developed in the interest of advancing educational science.